Bael Leaf Oil Increases AQP3 Expression and Exerts Wound-Healing Effect in Human Immortalized Keratinocytes - Kesornnoi, Budsarin; Prangsaengtong, Orawin; Chuvisitkul, Duangratana; Sitthithaworn, Worapan (Naresuan University Journal: Science and Technology (NUJST); Vol 31 No 3 (2023): July-September-2023DO - 10.14456/nujst.2023.26, 2023)
Bael ( Aegle marmelos L. Corrêa, Family Rutaceae) leaf oil has been reported to promote wound healing in keratinocyte cell models. The oil key components, according to GC-MS analysis, are trans-caryophyllene and limonene. In this study, we investigated the mechanism by which bael leaf oil and its key components aid wound healing by focusing on the water channel aquaporin-3 (AQP3), which is crucial for maintaining skin hydration and identifying the active component responsible for the activity. To this objective, keratinocyte (HaCaT) cells were grown in media containing 2% FBS and subjected to a wound healing assay. The expression of AQP3 mRNA in the cells was observed using RT-real-time PCR. The results demonstrated that trans-caryophyllene and bael leaf oil significantly stimulated keratinocytes to close the wound ( p <0.05 vs . vehicle group) and enhanced the level of AQP3 mRNA expression. It suggests that trans-caryophyllene, at least among the components of bael leaf oil, enhances the wound healing action instigated by the bael leaf oil, and that this effect is associated with the water channel aquaporin-3. Keywords : bael leaf oil, trans-caryophyllene, HaCaT, wound healing, aquaporin-3